Ta’ziz almuhadathat alhiwariah bi al-lughah al-arabiyaah min khilal "karir ba’dy" bayna al-muta’alimin al-mukatsafiin - Asrofik, Asrofik; Sa'diyah, Halimatus; Ma'arif, A. Samsul; Suroiyah, Evi Nurus (Lugawiyyat, 2025)
ABSTRACT Speaking skills are a fundamental aspect of language learning, especially for students in intensive programs who are required to communicate effectively. However, many students still struggle to speak fluently, accurately, and confidently. This study aims to improve students' speaking skills through the implementation of the Repeat After Me game. The Classroom Action Research (CAR) method was implemented in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects were 40 students in an intensive language program at a state university. Data were collected through observation, speaking performance assessments, self-confidence questionnaires, and interviews. The results showed significant improvements in pronunciation, intonation, and fluency, as well as increased student confidence in speaking. The average speaking score increased from 2.1 (pre-action) to 3.5 (cycle II), while confidence increased from 38% to 77.5%. The Repeat After Me game proved to be an effective, interactive, and enjoyable method for improving students' speaking skills. This study recommends the widespread use of similar methods in language classes, particularly in intensive learning contexts.Keywords: Speaking Skills, Repeat After Me, Language Games, Self-Confidence.